Competitive strategies in community forestry: leveraging through second-tier collectie enterprises in Mexico and Guatemala - Tanaka, Hiroyuki (2012)
Tesis (Ph. D. )-- CATIE. Escuela de Posgrado, Turrialba (Costa Rica), University of Idaho, 2012